Membaca Narasi Penciptaan Mazmur 19:1-6 Melalui Perspektif Kosmologi Intelligent Design: Irreducible Complexity - Yahya Afandi (Jurnal Teologi Gracia Deo, 2020)
This article examines: is science and theology so wide apart from each other; is the suffering of bible scholars who have a "second class" status in academic conversation impossible to end? The advancement of science which should illuminate the theological-biblical notions which are textually unexplainable in scientific detail has in fact created such a sharp split point. The idea of Intelligent design: irreducible complexity promoted by Michael J. Behe provides a kind of “theistic interstice" that can be used as a lens to see the existence of an intelligent designer of the universe narrated in Psalms 19: 1-6. The existed complexity, cannot be reduced because the condition itself is threatening the universal system. This article concludes with the identification: if the assumptions of an intelligent designer who refers to God is considered too premature; the framework of an intelligent designer then provides an imaginative space to grapple with the possibility of His involvement in the universe. Abstrak Artikel ini mempertanyakan ulang: Apakah ilmu pengetahuan dan teologi alkitabiah sudah sedemikian jauh terpisah satu sama lain? Apakah penderitaan para sarjana kitab suci yang diklaim berstasus “kelas dua” dalam percakapan akademik mustahil diakhiri? Kemajuan ilmu pengetahuan yang semestinya menerangi terminologi teologis-alkitabiah, yang barangkali memang secara tekstual tidak dijelaskan secara detail-ilmiah khususnya isu kosmologi dan kosmogoni, nyatanya justru telah menciptakan titik pisah yang begitu tajam. Gagasan kosmologi Intelligent design: irreducible complexity yang diusung oleh Michael J. Behe memberi semacam “celah teistik” yang dapat dipergunakan sebagai lensa untuk melihat kemungkinan keberadaan Sang Perancang Cerdas semesta raya dalam narasi Mazmur 19:1-6. Kerumitan yang ada, tidak dapat dikurangi, tidak boleh tidak ada. Mengingat situasi tersebut justru berpeluang mengancam sistem semesta. Artikel ini diakhiri dengan identifikasi, bahwa jika dugaan perancang cerdas yang merujuk kepada keberadaan Tuhan dinilai terlalu prematur, maka pemikiran intelligent designer menyediakan ruang imajinatif-intelektual untuk menggumuli kemungkinan keberadaan dan keterlibatan-Nya atas semesta.